Catalytic and photocatalytic oxidation of diphenyl sulphide to diphenyl sulfoxide over titanium dioxide doped with vanadium, zinc, and tin. Issue 7 (23rd January 2020) - Radko, Marcelina; Kowalczyk, Andrzej; Mikrut, Paweł; Witkowski, Stefan; Mozgawa, Włodzimierz; Macyk, Wojciech; Chmielarz, Lucjan
Abstract : Phase transitions of rutile and anatase were directed by V, Zn and Sn admixtures. Rutile containing catalysts were more active in Ph2 S oxidation than pure anatase samples. Efficiency of Ph2 S oxidation was significantly improved under UV radiation. Abstract : Samples of TiO2 (P25) doped with zinc, tin, and vanadium, thermally treated at 550 °C for 6 h, were tested as catalysts and photocatalysts for the oxidation of diphenyl sulphide to diphenyl sulfoxide and sulfone, using hydrogen peroxide as an oxidation agent. Thermal treatment of pure TiO2 and its vanadium-doped forms resulted in a decrease of anatase and an increase of rutile content. The opposite effect was observed for TiO2 doped with zinc or tin, where thermal treatment resulted in the rutile to anatase phase transition. The role of V, Zn, and Sn admixtures as TiO2 phase-composition controllers was postulated. The catalytic and photocatalytic activity was found to be influenced more by the rutile and anatase contents of the samples than the presence of admixtures. The rutile-containing samples, TiO2 and V-TiO2, presented much better activity in the catalytic oxidation of diphenyl sulphide compared with the catalysts that only contained the anatase phase, Sn-TiO2 and Zn-TiO2 . The reaction efficiency was significantly improved under UV radiation. In this case, the best photocatalytic activity was found for calcined TiO2, containing both anatase and rutile components. An increase in rutile content, observed in the vanadium-doped TiO2, decreased the efficiency of the photocatalytic diphenyl sulphide oxidation. Thus, the presence of both anatase and rutile phases, with their favourable contributions, typical for P25, is necessary for the effective oxidation of Ph2 S to Ph2 SO. Moreover, it was shown that for the second oxidation stage, Ph2 SO to Ph2 SO2, the presence of the rutile phase is very important.